Circulating Antibodies to Skin Bacteria Detected by Serological Lateral Flow Immunoassays Differentially Correlated With Bacterial Abundance - Huang, Ryan Yuki; Lee, Chuen Neng; Moochhala, Shabbir (Frontiers in Microbiology, 2021)
The serological lateral flow immunoassay (LFIA) was used to detect circulating antibodies to skin bacteria. Next-generation sequencing (NGS) analysis of the skin microbiome revealed a high relative abundance of Cutibacterium acnes (C. acnes) but low abundance of Staphylococcus aureus (S. aureus) and Corynebacterium aurimucosum (C. aurimucosum) on human facial samples. Yet, results from both LFIA and antibody titer quantification in 96-well microplates illustrated antibody titers that were not correspondent, and instead negatively correlated, to their respective abundance with human blood containing higher concentrations of antibodies to both S. aureus and C. arurimucosum than C. acnes. Acne vulgaris develops several unique microbial and cellular features, but its correlation with circulating antibodies to bacteria in the pilosebaceous unit remains unknown. Results here revealed that antibodies to C. acnes and S. aureus were approximately 3-fold higher and 1.5-fold lower, respectively, in acne patients than in healthy subjects. Although the results can be further validated by larger sample sizes, the proof-of-concept study demonstrates a new-found discrepancy between the abundance of skin bacteria and amounts of their corresponding antibodies. And in light of acne-correlated amplified titers of specific anti-commensal antibodies, we highlight that profiling these antibodies in the pilosebaceous unit by LFIAs may provide a unique signature for monitoring acne vulgaris.